Advanced UAV aerodynamics, flight stability, and control : novel concepts, theory and applications - Marques, Pascual; Da Ronch, Andrea (Aerospace series (Chichester, England), 2017)
Presenting emerging aerospace technologies in the rapidly growing field of unmanned aircraft engineering, this book describes the findings and innovations accomplished in current research programs and industry applications throughout the world. --